PEMBERIAN KOMPRES JAHE DALAM MENGURANGI NYERI SENDI PADA LANSIA DI UPT PSTW KHUSNUL KHOTIMAH PEKANBARU - Tri Siwi KN (Sistem Informasi, 2016)
Gout and rheumatoid arthritis is a disease that is often encountered in the community, one of them on the elderly (the elderly) are characterized by pain that occurs repeatedly in the joints. Ginger compress can be used as a nonpharmacological measures to deal with the pain. This study aims to determine the effectiveness of ginger compress in reducing joint pain in the elderly in UPT PSTW Khusnul Khotimah Pekanbaru. This design of research is a quasi experiment with sampling total sampling with 16 respondents. Data collection tool using pain scale test pre and post administration of ginger compress. The research result shows that the average intensity of joint pain before and after the ginger compress is 2.500. The test results obtained statistical p value = 0.000 where p <α 0:05. this means that there are differences in average significant difference between the intensity of joint pain in the elderly before and after the ginger compress. Is expected to more elderly for routine use as a ginger compress nonpharmacological measures pain in the joints.